Advancements in Computer-Aided Drug Design: A Comprehensive Review - Yadav, Aniket; Singh, Anju; Rajendiran, A.; Pal, Ruchi; Kumar, Avdhesh; Sachin, Sachin; Bhadauria, Himanshi (Journal of Neonatal Surgery, 2025)
In the last few years, the Computer-Aided Drug Design and Discovery is many successes rates. Computational drug design is used for drug lead discovery in various pharmaceutical industries and academic institutions. In the current era of medication research and discovery, structural data is crucial. Various docking programs have been created to visualize the three-dimensional structure of molecules. Drug design software that runs on computers is used to examine the docking score. It is a virtual screening technique for target molecule orientation, conformation, and position that is based on structure. The idea of ligand and protein docking is novel. Biological pathway analysis, de Novo drug design, and lead molecule optimization are the three complex aspects of the molecular docking approach